Underwater Acoustic Digital Signal Processing and Communication Systems - Istepanian, Robert S. H.; Stojanovic, Milica (Springer US, 2002)
Underwater acoustic digital signal processing and communications is an area of applied research that has witnessed major advances over the past decade. Rapid developments in this area were made possible by the use of powerful digital signal processors (DSPs) whose speed, computational power and portability allowed efficient implementation of complex signal processing algorithms and experimental demonstration of their performance in a variety of underwater environments. The early results served as a motivation for the development of new and improved signal processing methods for underwater applications, which today range from classical of autonomous underwater vehicles and sonar signal processing, to remote control underwater wireless communications. This book presents the diverse areas of underwater acoustic signal processing and communication systems through a collection of contributions from prominent researchers in these areas. Their results, both new and those published over the past few years, have been assembled to provide what we hope is a comprehensive overview of the recent developments in the field. The book is intended for a general audience of researchers, engineers and students working in the areas of underwater acoustic signal processing. It requires the reader to have a basic understanding of the digital signal processing concepts. Each topic is treated from a theoretical perspective, followed by practical implementation details. We hope that the book can serve both as a study text and an academic reference
Keywords: Engineering; Signal, Image and Speech Processing; Electrical Engineering; Offshore Engineering; Oceanography; Building construction; Electrical engineering; Hydroakustik; Digitale Signalverarbeitung